2021
DOI: 10.3390/fishes6030023
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Chemical Composition, Histology and Antioxidant Genes of Atlantic Salmon (Salmo salar) Fed Whole or Pre-Processed Nannochloropsis oceanica and Tetraselmis sp.

Abstract: New sustainable feed ingredients are a necessity for the salmon aquaculture industry. In this study, we examined the effect of pre-extrusion processing of two microalgae, Nannochloropsis oceanica and Tetraselmis sp., on the growth, fatty acid content in the flesh and health of Atlantic salmon. The fish were fed one of the following five diets for nine weeks: (1) CO: a fish meal-based control (basal) diet, (2) NU: a Nannochloropsis diet, (3) NE: a pre-extruded Nannochloropsis diet, (4) TU: a Tetraselmis diet, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 92 publications
3
7
0
Order By: Relevance
“…The high Sod1 concentration in liver of fish fed C. vulgaris intact and T. chuii acutely after salinity change (20 h in seawater) may provide a better oxidative state during this time period but protein levels potentially decreased 2 weeks in seawater because lower ROS levels were subsequently present. In line with these results, previous research on salmon fed with a pre-extruded Tetraselmis diet also revealed significantly induced sod1 expression in the liver ( Sørensen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…The high Sod1 concentration in liver of fish fed C. vulgaris intact and T. chuii acutely after salinity change (20 h in seawater) may provide a better oxidative state during this time period but protein levels potentially decreased 2 weeks in seawater because lower ROS levels were subsequently present. In line with these results, previous research on salmon fed with a pre-extruded Tetraselmis diet also revealed significantly induced sod1 expression in the liver ( Sørensen et al, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…In another study, serum SOD and GPx activities recorded the highest values in Nile tilapia fed on a diet partially replaced with N. oculata at 5% for 60 days compared to the control fish [ 56 ]. Such GPx upregulation effect was not evident in the liver of whole N. oculata -fed Atlantic Salmon ( Salmo salar ) at 30% for 60 days [ 79 ]. Similar induction in the expression of Hsp70 was evident in the liver of whole N. oculata at 10% in Nile tilapia under naïve conditions for 4 weeks [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Arctic charr, we registered an opposite pattern: the levels of DHA and EPA were lower in the Gyda River, indicating that other factors may contribute to this result. Indeed, nutrition, in some cases, plays a more important role in driving fatty acid signatures in fish [30,31]. However, in most cases, it is a combination of both nutrition and temperature that has the greatest influence on the fatty acid composition in fish [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Fish products, especially flesh, have long been recognized as important sources of lowfat protein and essential fatty acids, particularly n-3 and n-6 PUFAs, among which EPA and DHA are the most important [9,31]. Many previous studies have demonstrated that PUFAs can act as a preventative measure against cardiovascular disorders and hypertension in adults and are vital in fetal brain development [43,44].…”
Section: Discussionmentioning
confidence: 99%